Calling Out Displays and Disclaimers of Aggression - Innocenti, Beth (Informal Logic)

(untitled) (Informal Logic, 2026)
How can arguers address aggression to “allow rationality to play its intended role” (Hundleby 2013, p. 259)? I argue that a normative pragmatic approach to the question avoids the pitfalls of idealization and fallacy approaches and provides answers. To illustrate, I analyze an exemplary response to misogynistic aggression and show that its efficacy lies in undertaking and warranting a commitment to the judgment that the bad behavior deserves public attention and moral outrage. I conclude by providing implications of Hundleby’s work for argumentation researchers working on tools for modeling and assessing argumentation.